A before and after in valvular dysfunction and arteriovenous shunt closure in functioning kidney transplant recipients. - Cruz Abascal, Rafael Enrique; Fernández Olivares, Miguel; Ramírez Gómez, José Ignacio; Gutiérrez Gutiérrez, Carlos; Pérez Delgado, Lisbel; González Cárdenas, Yuniel; Hernández Fernández, Milagro Estrella; Batista Hernández, Raunel; González Benavídez, Cecilio (Revista Cubana de Nefrología, 2024)
Introduction: Cardiovascular complications are the leading cause of mortality in renal transplant recipients. Objective: To determine the possible influence of closure of the arteriovenous shunt for hemodialysis on valvular dysfunction in functional renal transplant recipients. Method: A descriptive, longitudinal and prospective investigation was carried out at “Arnaldo Milián Castro” University Hospital, Villa Clara Province, Cuba, from November 2012 to April 2015. It had involved 25 patients with functional renal transplant followed by more than one year with a stable function and with no foreseeable risk of complications at a specialized clinic, who underwent arteriovenous shunt closure for hemodialysis. Thirteen patients (52 %) had multiple cardiac valvular dysfunction, whereas in 12 (48 %), there was a single alteration. Results: The age group prevailed between 51 and 60 years old, 10 (40 %), 18, white skin color (72 %). The causes of chronic renal disease: unknown, hypertensive nephropathy and autosomal dominant polycystic kidney disease were demonstrated in five patients each (20 %). Light tricuspid insufficiency was the most frequent valvulopathy; 6 (50 %) with shunt in the bend of the elbow and the time of stay shorter and greater than 6 years was evidenced in three; (25 %). Their patterns were 75 % improved six months after shunt closure (x2 = 4.762 pα = 0.236) and (x2 = 4.286 pα = 0.378) respectively. Multiple valvular dysfunctions, its relation to the location and the time of permanence of the shunt, before and after closure, were verified in 13 patients. The tricuspid insufficiency with light mitral was predominant in 4; (30.8 %). In three, no modification of the lesional pattern was observed at six months, while one did, in a partial way, without any relation to the localization site and the time of permanence of the fistula. Valvular affection, its relation to mean shunt time, time after transplantation and the presence or absence of arterial hypertension, showed a strong correlation between mean shunt time and post-transplant time for single cardiac alterations (5.5 and 2.6 years, respectively) at as for multiples (9.2 and 5.2 years respectively). Ten patients with single lesions were hypertensive, of whom eight received monotherapy and two double or triple, whereas in the multiple lesion; two were treated with one drug and seven with two or more agents (x2 = 6.343 pα = 0.023). Conclusions: Valvular dysfunctions, single and multiple, in a generally, modified their patterns when comparing them, before and after shunt closure, towards others of less severity. The mean time of the transplant and fistula, associated to arterial hypertension with requirements of two or more antihypertensive agents was found predominantly in multiple valvular dysfunctions.